Effects of different substrates on the morphological characteristics and proximate content of Pleurotus pulminarius. Food Science and Quality Management - Bakare, Mufutau Kolawole; A. O., Oluduro; Omoboye, Olumide; Leramo, Adefemi Joseph (international journal of proximate content of Pleurotus pulminarius, 2023)
journal of; Effects of different substrates on the morphological characteristics and proximate content of Pleurotus pulminarius. Food Science and Quality Management ;56 pages.